An unsteady stall-delay methodology for floating offshore wind turbines - Abdulqadir Aziz Singapore Wala (2021)
Stall-delay is a known phenomenon in wind turbines, and has been associated with the Coriolis effect along the blade, which contributes to the suppression of flow separation. Floating offshore wind turbines (FOWTs) operate in unsteady environments due to 6 degree-of-freedom platform motions. This results in unsteady airfoil effects and a non-static stall delay effect that would be in constant flux due to the changing tip speed ratio of the wind turbine. To ensure an accurate assessment of wind turbine aerodynamics, the stall delay effect needs to be accounted for at every time step, and not before a computation is performed as is traditionally done for wind turbine aerodynamics computation using BEM. The commonly used Beddoes-Leishman model for unsteady airfoil effects, however, is based on static aerodynamics data, but this would be constantly changing with a changing stall-delay. Thus, a combined Beddoes-Leishman and Du & Selig model is proposed to reconcile the shifting static aerodynamics coefficients of the airfoil cross-sections of wind turbine blades with the unsteady airfoil effect.